2017
DOI: 10.1021/acs.jmedchem.7b00205
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between β2-Adrenoceptor Ligands and Membrane: Atomic-Level Insights from Magic-Angle Spinning NMR

Abstract: To understand the relationship between structural properties of the β2-adrenoceptor ligands and their interactions with membranes, we have investigated the location and distribution of five β2 agonists with distinct clinical durations and onsets of action (indacaterol, two indacaterol analogues, salmeterol and formoterol) in monounsaturated model membranes using magic angle spinning NMR to measure these interactions through both H nuclear Overhauser enhancement (NOE) and paramagnetic relaxation enhancement (PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…S1). The specific locations and orientations of salmeterol and formoterol are in good agreement with a magicangle spinning NMR study that showed a similar depth and orientation for both the molecules (Yan et al, 2017). The difference in bilayer depths resulted in distinct orientations of their saligenin heads and markedly different interactions with the polar and alkyl lipid functional groups (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…S1). The specific locations and orientations of salmeterol and formoterol are in good agreement with a magicangle spinning NMR study that showed a similar depth and orientation for both the molecules (Yan et al, 2017). The difference in bilayer depths resulted in distinct orientations of their saligenin heads and markedly different interactions with the polar and alkyl lipid functional groups (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…High blood pressure treatment, Angiotensin II AT1 receptor Losartan [191,192], Candesartan [193] High blood pressure treatment, β-adrenergic receptors, GPCR Acebutolol [194], Alprenolol [148,195,196], AS408 [197], Atenolol [148,196,198,199], Carazolol [200], Formoterol [201], Idacaterol and its analogs [201], Metoprolol [196], Nadolol [196], Oxprenolol [194], Pindolol [148,196], Propranolol [194,196,202], Salbutamol [199], Salmeterol [201] High blood pressure treatment Amlodipine [198,203], Lisinopril [198], Debrisoquine [132] Anticancer drug…”
Section: Application and Target Drugs And Pharmaceuticsmentioning
confidence: 99%